PELAKSANAAN PROSEDUR KERJA ROOMBOY DI PREMIER BASKO HOTEL KOTA PADANG - Setiawati, Desi Eka; Chair, Ira Meirina; Waryono, Waryono (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
This research beginning from the information that researchers get the guest comment by September-December 2013 occurred guest complaints related to work procedures roomboy, covering room cleanliness, guest supplies completeness, neatness, and roomboy services. While working procedures roomboy can be seen from the standard operational procedure, consisting of grooming and behavior, preperation trolley cart, striping & dusting, making bed, cleaning the bath room, set up a guest supplies and rechecking. This research aims to describe how the implementation of work procedures roomboy Premier Basko Hotel in Padang.This research is a descriptive research with qualitative methods. This research was conducted in the Premier Basko Hotel Padang. Sample data source is roomboy, floor supervisor, and executive housekeeper at Premier Basko Hotel Padang. Data was collected by observation, interviews, and documentation of data subsequently analyzed using Miles and Huberman models by performing three stages: data reduction, data display, and conclusion.The research concluded that in general the implementation of work procedures roomboy namely: 1) There are eleven roomboy 18.1% of the working procedures that do not run well on the implementation of the grooming, 2) There are 72.7 % of the eleven roomboy not work properly implement procedures and right on routine preparation trolley cart, 3) There are 45.4 % of the eleven roomboy striping that does not do well and properly, and in the implementation of dusting all roomboy already doing well and in accordance with procedures, 4) There are 81.8 % of the eleven roomboy who do not perform the procedure making the bed is good and true, 5) 100 % or all roomboy not perform the cleaning procedure with a good bath room and not in accordance with the working procedures, 6) There are 63.6 % of the eleven who did seet up roomboy guest supplies are not in accordance with the working procedures, 7) There are 27.2 % of the eleven roomboy rechecking procedure that does not run well and was not in accordance with the prescribed procedure. The conclusion of this research is still a lack of understanding on the implementation of work procedures roomboy makeup room on the status of vacant dirty rooms at Premier Basko Hotel Padang.